Pengaruh Deskripsi Kerja, Spesifikasi Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Goldwell Plastic Batam - Kervin Kervin; Wasiman Wasiman (Komunitas Dosen Indonesia, 2023)
implementation of all agency activities or activities, so that they are managed properly through Human Resource Management. Employee performance is what employees do or don't do that affect how much they contribute to the organization, including output quality, output quantity, output period, presence at work, and cooperative attitude. The aim of this study was to determine the effect of job descriptions, job specifications, and work discipline on employee performance at PT Goldwell Plastic Batam. The sample for this study used 110 respondents to employees at PT Goldwell Plastic Batam using the sampling technique. By using SPSS 25 software, data analysis techniques include descriptive statistical tests, data quality tests, classical assumption tests, influence tests, and hypothesis testing. Based on the results of the study, it can be concluded that job descriptions, job specifications and work discipline jointly have a significant effect on employee performance at PT Goldwell Plastic Batam